Eye lens radiation exposure of the medical staff performing interventional urology procedures with an over-couch X-ray tube. (November 2017) - Medici, S.; Pitzschke, A.; Cherbuin, N.; Boldini, M.; Sans-Merce, M.; Damet, J.
Highlights: The eye lens exposure of the urology medical staff is assessed using OSL dosimeters. The relation between eye lens/chest dose and DAP for over-couch systems is discussed. The chest dose may be a non-conservative estimator of the eye lens dose for nurses and anaesthetist. The annual eye lens doses for physicians and instrumentalist nurses are above 6 mSv. Abstract: The purpose of this work was to estimate the eye lens radiation exposure of the medical staff during interventional urology procedures. The measurements were carried out for six medical staff members performing 33 fluoroscopically-guided procedures. All procedures were performed with the X-ray tube positioned over the couch. The dose equivalents ( H p ( 0.07 ) ) were measured at the eye level using optically stimulated luminescent (OSL) dosimeters and at the chest level with OSL dosimeters placed over the protective apron. The ratio of the dose measured close to the eye lens and on the chest was determined. The annual eye lens dose was estimated based on the workload in the service. For the physician and the instrumentalist nurse, the eye to chest dose ratios were 0.9 ± 0.4 and 2.6 ± 1.6 ( k = 2), respectively. The average doses per procedure received by the eye lens were 78 ± 24 μ Sv and 38 ± 18 μ Sv, respectively. The eye lens dose per DAP was 8.4 ± 17.5 μ Sv/(Gy · cm 2 ) for the physician and 4.1 ± 8.7 μ Sv/(Gy · cm 2 ) for the instrumentalist nurse. The results indicate that the eye lens to chest dose ratio greatly varies according to the staff function and that the dose equivalent measured by the personal dosimeter worn on the chest may underestimate the eye lens dose of some medical staff members.